Nutritional status, muscle strength and functional capacity in patients with multiple myeloma - Oliveira, Pollyane Caixeta de; Araújo, Alorna Sales de; Stringhini, Maria Luiza Ferreira; Machado, Malaine Morais Alves; Vieira, Liana Lima; Martins, Karine Anusca; Tavares, July-Ana Souza (O Mundo da Saúde, 2024)
Multiple myeloma is a malignant neoplasm characterized by the clonal proliferation of plasma cells in the bone marrow. The objective of this study was to evaluate possible associations between nutritional status, muscle strength and functional capacity of outpatients with multiple myeloma. This is a cross-sectional study carried out on a non-probabilistic sample of patients with multiple myeloma treated at Hospital das Clínicas, in Goiânia. Data were collected between August and December 2015, using interviews and information from medical records. Nutritional status was assessed using the Patient Generated Subjective Global Assessment; muscular strength measured using Hand Grip Strength and functional capacity, using the Karnofsky Performance Scale. The study was approved by the Ethics and Research Committee of that hospital. 52 patients were evaluated, of which 48.1% were malnourished, 30.8% had low muscle strength and 73.1% had impaired functional capacity. Muscle strength and functional capacity were lower in malnourished individuals. It was observed that those who used corticosteroids were 18% less likely to become malnourished (OR=0.18; CI=0.05-0.62; p=0.011), however, it is important to consider the possible causes of bias; on the other hand, patients with low muscle strength or undergoing chemotherapy were approximately four times more likely to be malnourished, respectively (OR=3.46; CI=0.99-12.08; p=0.047) (OR=3.64; CI=1.13-11.69; p=0.027). It was concluded that malnutrition is common in patients with multiple myeloma, indicating the pressing need for appropriate and early nutritional intervention.